A Trade-Based Analysis of the Economic Impact of Non-Compliance with Illegal, Unreported and Unregulated Fishing : The Case of Vietnam - World Bank (World Bank, Washington, DC, 2021)
Illegal, unreported and unregulated (IUU) fishing is a threat to the sustainable use of fishing resources. To eliminate the destructive fishing practices, the whole value chain of fish trade needs to be well regulated. Trade-related policy measures show potential for contributing towards the elimination of unsustainable fishing practices. The EU’s launch of the IUU-combating fishing program and the introduction of measures to deal with countries that exploit, produce and export fishery products with illegal fishing origin, is indispensable in addressing harmful trends and a concern of the whole world, especially the fishing community. The EU is a very important trading partner for Vietnam and major importer of Vietnam’s fish products, of which seafood plays an important role. The EU market helps pave the way for Vietnamese seafood to enter the world market. Vietnam’s seafood export to the EU has increased sharply over the past twenty years. The year of 2017 marked a critical turning point for Vietnam’s fisheries when the EU issued a yellow card warning to Vietnam for not cooperating and making enough efforts to combat IUU fishing. There will be many other consequences from the IUU yellow card warning and the impact will be more serious if Vietnam does not remove the yellow card soon or receives a red card warning. The main objective of this study is to assess the economic impact of the IUU yellow card, and a possible red card, on Vietnam’s fisheries sector in the short term and medium term. The report also reviews the new challenges faced by the seafood sector as a result of the Coronavirus Disease (COVID-19) pandemic.